Analisis flypaper effect pada belanja daerah pemerintah daerah kabupaten dan kota di provinsi Jawa Tengah Periode 2017-2019 - Fifi Armadani; Maryono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to show the possibility of the Flypaper Effect and the influence of local revenue, general allocation funds, special allocation funds, and profit sharing funds on regional expenditures. The population was taken from all regencies/cities in Central Java Province and a sample of 105 regencies/cities. The data used is taken from the Central Bureau of Statistics, Financial Statistics of the Sumatran and Java Regency/City Governments, Book 1 of 2017-2019. The analytical method used is descriptive statistical test, hypothesis testing, and multiple linear regression models. Based on the test results, it shows that Regional Original Income, General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds have a significant positive effect on Regional Expenditures and the Flypaper Effect phenomenon occurs in the Regency / City of Central Java Province.